Microbial community assembly differs across minerals in a rhizosphere microcosm. (10th September 2018) - Whitman, Thea; Neurath, Rachel; Perera, Adele; Chu‐Jacoby, Ilexis; Ning, Daliang; Zhou, Jizhong; Nico, Peter; Pett‐Ridge, Jennifer; Firestone, Mary
Summary: Mineral‐associated microbes drive many critical soil processes, including mineral weathering, soil aggregation and cycling of mineral‐sorbed organic matter. To investigate the interactions between soil minerals and microbes in the rhizosphere, we incubated three types of minerals (ferrihydrite, kaolinite and quartz) and a native soil mineral fraction near roots of a common Californian annual grass, Avena barbata, growing in its resident soil. We followed microbial colonization of these minerals for up to 2.5 months – the plant's lifespan. Bacteria and fungi that colonized mineral surfaces during this experiment differed across mineral types and differed from those in the background soil, implying that microbial colonization was the result of processes in addition to passive movement with water to mineral surfaces. Null model analysis revealed that dispersal limitation was a dominant factor structuring mineral‐associated microbial communities for all mineral types. Once bacteria arrived at a mineral surface, capacity for rapid growth appeared important, as ribosomal copy number was significantly correlated with relative enrichment on minerals. Glomeromycota (a phylum associated with arbuscular mycorrhizal fungi) appeared to preferentially associate with ferrihydrite surfaces. The mechanisms enabling the colonization of soil minerals may be foundational in shaping the overall soil microbiome composition and development of persistent organic matter in soils.